2001
DOI: 10.1152/physiolgenomics.2001.4.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoglossal long-term facilitation differs between substrains of Sprague-Dawley rat

Abstract: Long-term facilitation (LTF) is a prolonged, serotonin-dependent augmentation of respiratory motor output following episodic hypoxia. Previous observations lead us to hypothesize that LTF is subject to genetic influences and, as a result, differs between Sprague-Dawley (SD) rats from two vendors, Harlan (H) and Charles River Laboratories/Sasco (CRL/S). Using a blinded experimental design, we recorded integrated phrenic (integralPhr) and hypoglossal neurograms in anesthetized, vagotomized, paralyzed, and ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 33 publications
7
71
1
Order By: Relevance
“…However, it is well known that SD substrains, including SD substrains from the same provider, may show marked differences in a variety of responses (37)(38)(39)(40)(41)(42). SD rats are randomly outbred; hence, allelic variations can occur across vendors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well known that SD substrains, including SD substrains from the same provider, may show marked differences in a variety of responses (37)(38)(39)(40)(41)(42). SD rats are randomly outbred; hence, allelic variations can occur across vendors.…”
Section: Discussionmentioning
confidence: 99%
“…Because rat strain and substrain differences influence the magnitude of respiratory LTF (Fuller et al, 2001b) and the severity of motor and sensory impairment after SCI (Gorman et al, 2001;Mills et al, 2001), the choice of rat strain could influence the ability of intermittent hypoxia to induce pLTF after chronic SCI. To account for this possibility, we studied both inbred Lewis (LW) and outbred Sprague Dawley (SD) rats.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence is also accumulating that genotype can influence respiratory plasticity. For example, experiments on Sprague-Dawley rats from different colonies (60,61) revealed that phrenic and hypoglossal LTF after intermittent hypoxia differ substantially between rat substrains. Mutations in selected genes can also influence respiratory plasticity (112,121,122).…”
Section: Genotype Can Influence Plasticitymentioning
confidence: 99%